The analysis of the current state of accidents at work in Poland in the years 2002–2014 (Economic and Political Thought, 2016)
The aim of the paper is to elaborate the current state of accidents at workin Poland in the years 2002–2014. The emphasis is placed on the analysis ofthe level, structure and trends in accidents at work in Poland. In the articlealso causes and effects of the occupational accidents are discussed.The article consists of 4 main parts: introduction, information in the fieldof registration of accidents at work – European and national context, occupationalaccidents in numbers and conclusions. The main source of empiricaldata were statistics provided by the Central Statistical Office in Poland.The Author has proven that in the considered time period working conditionsin relation to the accidents at work did not improve significantly. Workin Poland did not become safer. In the years 2002–2014 the total number ofoccupational accidents and the overall ratio of accidents at work (the numberof the injured persons per 1,000 of the employed) did not change a lot.